An Analysis of Figurative Language in Santa Esmeralda’s Song Lyrics Entitled You’re My Everything - Sukmono Bayu Adhi (TEKNOSASTIK, 2022)
This study aims to analyze the figurative language and its meaning contained in the lyrics of the song "You're My Everything". It is descriptive qualitative research where the data taken comes from a song lyrics website. The data used in this study are the lyrics of a song released in 1977 entitled “You're my everything” which was sung by Santa Esmeralda on Esmeralda on the album Don't Let Me Be Misunderstood. The result of this study indicates that there are nine data sets that contain 14 figurative languages consisting of four types, namely: alliteration (six items), hyperbole (four items), pleonasm (three items), and synthesis (one item). Thus, the results of this study show that 42,8 percent is alliteration, 28,5 percent is hyperbole, 21,5 percent is a pleonasm, and 7,2 percent is the antithesis.